2017
DOI: 10.5455/msm.2017.29.201-206
|View full text |Cite
|
Sign up to set email alerts
|

Health System Reform Plan and Performance of Hospitals: an Iranian Case Study

Abstract: Background:Health system reform is essential to make desired Changes. In Iran, first phase of Health Reform Plan (HRP) was implemented in hospitals affiliated with Ministry of Health and Medical Education (MHME) in 2014.Aim:The present study was carried out to evaluate the performance of hospitals affiliated with Urmia University of Medical Sciences at the time of the implementation of HRP.Methods:This cross-sectional study carried out in two stages, before (2012- 2013) and during (2014- 2015) implementation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…This information informs the program managers and policymakers and would provide the grounds for monitoring the national goals and assessing relevant policies. Timely monitoring and evaluation of reforms can provide evidence to guide the more proper implementation of reforms (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…This information informs the program managers and policymakers and would provide the grounds for monitoring the national goals and assessing relevant policies. Timely monitoring and evaluation of reforms can provide evidence to guide the more proper implementation of reforms (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] Studies in Iranian cities Uromieh, Kurdistan, and Yazd showed that this aspect of HSRP (less out-of-pocket payment) was the main cause of satisfaction in the public so that the respondents were satisfied with the expenses of medical services. [ 9 18 19 ] However, the plan was later faced with challenges mostly due to heavy financial load on the government, changes in insurance contracts, and hospital expenses. [ 15 16 ] According to the Islamic Republic of Iran National Research Institute, after 2 years since the commencement of plan, direct payment by Iranian households for health services was 5.34%, while based on the WHO computation method, payment capacity by households should be 7% at most.…”
Section: Resultsmentioning
confidence: 99%
“…[ 29 ] Patients thronging public health facilities while these facilities are not equipped to support the increasing demand was one of the main causes of dissatisfaction of nurses with their salary. [ 18 24 28 ] Limitations on recruiting new personnel and nurses, which are still in place, added to the complexity. [ 6 ] Given the excessive increase in the workload, nurses demand a higher salary and welfare, along with just and equal organizational promotion.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the health system reform plan started to operate to expand healthcare justice, improve healthcare quality, and increase the satisfaction of patients (5). Based on this plan, 11 service packages are provided to the people via healthcare centers and urban health posts: Self-caring services in worshiping, living, working, educating, and entertaining areas, early diagnostic services for diseases and risk factors, evaluation and diagnostic services for chronic and seasonal diseases, caring services for pregnant and nursing mothers, children and teenagers, middle-aged people and elderlies, psychological consultation services for cov-ered population, consultation services for healthy nutrition and physical activities, services for social caring consultation, services for improving the management system of contagious diseases, dental health services, working area healthcare services, and healthcare services for disasters (6).…”
Section: Introductionmentioning
confidence: 99%